(untitled) (Research, Society and Development, 2022)
This study determined whether adding an immunological homeopathic product (Imunorgan®) to the calf diet during the first months of life improves immune reactions, antioxidant responses, metabolism, and growth. The 12 calves with an average of 36±4 kg and 30 days of life, were divided into a control (n=6) and treatment (n=6) group who received the homeopathic product in milk during the first 30 days and subsequently in the concentrate (providing 10 g/day of the immunological homeopathic, based on Arsenicum album, Baptisia tinctoria, Calcarea carbonica, Iodum purum, Medicago sativa, Mercurius solubilis, Nux vomica, Pyrogenium, and sucrose vehicle). The animals in the treatment group had more significant body weight gain from 1 to 30 days of the experiment (p≤0.05). There was a treatment effect on hematologic results, with hemoglobin concentration showing major treatment x day interaction on day 90 (p≤0.05). Leukocyte, neutrophil, and lymphocyte counts were higher in the treatment group (p≤0.05). The albumin concentration in the treatment group animals was lower than in the control group (p≤0.05). The globulin concentration was higher in the treatment group (p≤0.05). There was a treatment x day interaction for the concentration of protein thiols on days 30, 60, and 90, with higher serum levels in calves in the treatment group (p≤0.05). Serum levels of reactive oxygen species were lower in calves of the treatment group (p≤0.05). The animals of the treated group showed a higher concentration of IgA. During the experiment, levels of ceruloplasmin, haptoglobin, transferrin, acid glycoprotein, and light-chain IgG also changed (treatment x day interaction). These findings suggest that the homeopathic product stimulated immunological responses.